European Uunion Energy Security and Russia - N. A. Simonia; A. V. Torkunov (Vestnik MGIMO-Universiteta)
The article deals with the retrospective of relations between Russia, USA and EU in the sphere of energy security, as well as their interaction regarding the current political crisis in the Ukraine. Particular attention is paid to the evolution of the key actors'positions and the development of their relations within the framework of the regulatory regimes established by the most significant agreements in the energy sphere. In conclusion the authors claim that what they say in their article not only does substantially reinforce the arguments set forth by Professor Giuseppe Guarino, who argues about the negative consequences caused by the dictatorship of the Brussels's bureaucracy within the EU, but also inflicts another blow on the Maastricht Treaty and the Treaty of Lisbon in terms of external policy and trade, since the both Treaties were designed to convert the EU in a real competitor of the United States in the then forming multipolar World. The Brussel's bureaucracy, having turned into a dutiful instrument of the US geopolitical strategy, hindered the movement of the EU in that direction, while its dictatorship in energy security aggravates the crisis situation of the EU, almost pushing the EU to the brink of collapse and disintegration. We have lately witnessed an evolving and growing phenomenon of the so called "Euroscepticism". The results of the Europarliament elections in late May, 2014, were a graphic demonstration of the symptoms of this alarming for the EU disease, when the anti-EU parties in the four out 22 EU countries won the elections (France, United Kingdom, Denmark, and Greece) Those results, regardless of the panic headlines in mass media and statements like "shocking" or "earthquake" made by some politicians, were not able to significantly affect the nature of the European Parliament, though they can significantly complicate its work. This is so far the first "alarming bell" tolling for the EU.